2012 4th Workshop on Hyperspectral Image and Signal Processing (WHISPERS) 2012
DOI: 10.1109/whispers.2012.6874315
|View full text |Cite
|
Sign up to set email alerts
|

Unmanned aerial vehicle (UAV) hyperspectral remote sensing for dryland vegetation monitoring

Abstract: UAV-based hyperspectral remote sensing capabilities developed by the Idaho National Lab and Idaho State University, Boise Center Aerospace Lab, were recently tested via demonstration flights that explored the influence of altitude on geometric error, image mosaicking, and dryland vegetation classification.The test flights successfully acquired usable flightline data capable of supporting classifiable composite images. Unsupervised classification results support vegetation management objectives that rely on map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 9 publications
0
14
0
2
Order By: Relevance
“…In total, we downloaded 131 articles that were then re-checked to assess their relevance. Ultimately, we only found 18 original-research articles that assessed both understorey vegetation and used high resolution remote sensing (Table 1; [1,18,19,22,[36][37][38][39][40][41][42][43][44][45][46][47][48][49]). We reviewed all of them.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, we downloaded 131 articles that were then re-checked to assess their relevance. Ultimately, we only found 18 original-research articles that assessed both understorey vegetation and used high resolution remote sensing (Table 1; [1,18,19,22,[36][37][38][39][40][41][42][43][44][45][46][47][48][49]). We reviewed all of them.…”
Section: Resultsmentioning
confidence: 99%
“…Although hyperspectral data provides more opportunities to find spectral signatures with less overlap among species, the only two papers reviewed that used this type of data reported only partial successes. Lopatin et al [41] attributed their shortcomings to a relatively coarse spatial resolution, while Mitchell et al [44] attributed theirs to 'complications' on data acquisition and suggested better results could be attained by using a wider spectral range and monitoring at different phenological times.…”
Section: Spectral Sensitivitymentioning
confidence: 99%
“…Furthermore, hyperspectral sensors have been shrinking in size and weight, and their use onboard of UAVs has become feasible [26][27][28]. Recently, several studies have addressed the use of UAV hyperspectral sensors in vegetation [29,30], crop [31][32][33][34][35][36][37][38][39][40][41][42], forest monitoring [43], and wetland species mapping [44], etc. However, few specific results have been published on mapping mangrove species using UAV hyperspectral images.…”
Section: Introductionmentioning
confidence: 99%
“…UAV technology has been developing rapidly. A variety of sensors onboard UAV platforms have been implemented and there have been many research projects employing UAVs to collect hyperspectral [12][13][14] and thermal data [15,16]. Some researchers also used LiDAR sensors mounted on UAV platforms to collect elevation data and develop DEMs [17][18][19].…”
Section: Introductionmentioning
confidence: 99%